The Oder-Neisse problem : towards fair play in Central Europe - Wilpert, Friedrich von, 1893-1990 1893-1990 (Edition Atlantic-Forum, 1965)
This book is dedicated to the proposition that two wrongs can never make a right. The immediate wrongs involved are: Adolf Hitler's attack on Poland in 1939 and Communism's aggression against Europe since 1945. This book rejects both wrongs and proposes a new start based on fair play between two neighbors in Central Europe: Poland and Germany. - Introduction